2016
DOI: 10.1111/trf.13769
|View full text |Cite
|
Sign up to set email alerts
|

Continuous CD34+ cell collection by a new device is safe and more efficient than by a standard collection procedure: results of a two‐center, crossover, randomized trial

Abstract: The OPTIA CMNC collection procedure is safe and effective for the collection of CD34+ cells in G-CSF-mobilized donors and was superior to the COBE for CE1% and CE2%, collecting approximately 19 and 16% higher, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
29
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 22 publications
9
29
4
Order By: Relevance
“…PL and PL per liter of blood volume processed were both lower in the Spectra Optia group. Those results are in line with the finding from Cancelas et al and Brauninger et al but differed from Del Fante et al, who did not find any significant differences in PL between the COBE Spectra and the Spectra Optia devices. In our study, the lower PL and PL per liter of blood processed on the Spectra Optia may be explained by a lower volume of blood processed and a lower starting platelet count.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…PL and PL per liter of blood volume processed were both lower in the Spectra Optia group. Those results are in line with the finding from Cancelas et al and Brauninger et al but differed from Del Fante et al, who did not find any significant differences in PL between the COBE Spectra and the Spectra Optia devices. In our study, the lower PL and PL per liter of blood processed on the Spectra Optia may be explained by a lower volume of blood processed and a lower starting platelet count.…”
Section: Discussionsupporting
confidence: 90%
“…We have observed higher nontargeted cells contamination in the Spectra Optia group. This is contradictory with previously published studies, which mainly reported larger granulocyte and red blood cell (RBC) contaminations with the COBE Spectra device. Despite higher granulocyte contaminations in our Spectra Optia group, it remained lower than those reported by Del Fante et al (9.1 ± 16% on CMNC and 12.2 ± 19.1% on MNC) and within the range of Del Fante et al (3.8 (2.8‐6.4)%) for MNC products in 2013 .…”
Section: Discussioncontrasting
confidence: 88%
“…Our results showed no significant difference between the CE2 of the two devices (42% for Optia® CMNC versus 41.6% for COBE® Spectra). In a study of 23 healthy donors, Cancelas et al noted a CE2 of 62.4% for Optia® CMNC and 48.4% for COBE® Spectra (P < 0.001) . However, other studies in autologous collectors with hematologoic malignancies have noted a wide range of CE2 (44%‐56%) utilizing the two‐step Spectra Optia® system .…”
Section: Discussionmentioning
confidence: 98%
“…The results are comparable to published data in adults. Cancelas et al reported a 62% CE2 in healthy adult donors, Sanderson et al reported a CE2 of 48.5% in adult myeloma and lymphoma patients . A direct comparison of MNC and CMNS in adults has been published by Lisenko et al who reported in a retrospective analysis a CE2 of 39% to 50% in 72 patients with malignancies, which was not significantly different from the studied MNC group .…”
Section: Discussionmentioning
confidence: 83%